Analysis of Russel brand’s vlog on “The Truth About Pfizer’s Vaccines" - J. Valdez, Renalyn; A. Palagtiw, Diondy; T. Sacueza, Donnie (Penerbit Universiti Kebangsaan Malaysia, 2024)
The spread of misinformation is a growing concern in today's digital age. The Vlog by Russel Brand titled "The Truth about Pfizer's Vaccines" features various claims about the safety and efficacy of Pfizer's COVID-19 vaccine. The study sought to answer the question, “How does the Vlog “The Truth about Pfizer’s Vaccines” constructed for public understanding and engagement?” The study used Kenneth Burke’s Dramatism Theory to examine the arguments in Russel Brand’s Vlog. It analyzed both stated and implied messages and made an in-depth look at the underlying reasons and purpose of such messages and meaning-making. In this study, Brand’s Vlog on Pfizer’s vaccines was examined using Burke’s Pentad. The study used a qualitative design with Textual Analysis as a tool. Concepts of construction, understanding, and engagement were examined using Dramatic Pentad while understanding and engagement were analyzed using Identification and Guilt. The Vlog “The Truth about Pfizer’s Vaccines” was constructed for public awareness and engagement, not so much for understanding. The Vlog emphasized the possible conspiracy between academic scientists and pharmaceutical giants. It, however, failed to provide an understanding as to how the system operates given the health crisis, professional and ethical standards of industries and communities involved, and policies, programs, and regulations both in the private and public sectors. Overall, Brand’s Vlog appealed to the public with this formula: Keep the discussion simple, center on the message by repetition, and target the public’s emotions.